(untitled) (Gragoatá, 2019)
Queer rap has been shining in the homophobic world of hip-hop lately, especially in the contemporary New York music scene. Considered by many as the new kids on the block, queer rappers have been breaking down mainstream ways of composing, delivering and enacting rap tunes by working on more outwardly feminine performances characterized by ambivalence, hybridity and defiance. In this paper, we focus on how Rico Dalasam, a contemporary Brazilian rap performer, radicalizes this type of rupture, engaging in what we have termed ‘abject aesthetics’. The latter constitutes a spectacular semiotic landscape, in which mixed sexualities, genders, races, ethnicities, clothing styles, hair styles, rhythms, languages and registers interact. In fact, transperformances and transidiomaticity dominate his work, which we approach through a scalar sensitive lens (CARR; LEMPERT, 2016) and metapragmatic indexicality (SILVERSTEIN, 1993) as we analyze the artist’s lyrics, performances and their reception by different audiences. In doing so, we shed light on the smuggling of semiotic resources which subverts the usual circulation of linguistic and non-linguistic goods across borders. In particular, we discuss how Dalasam’s deterritorializing-multisemiotic enactments confront modernist epistemological and linguistic regimes by subverting logocentrism. The analysis focuses on the transit between the so-called margin and center and on the enigmatic meanings generated by the mixture of languages and performances. As a whole, these aspects leave interactants in a state of uncertainty since the assembled resources are not directly intelligible in a conventional sense, most often preventing straightforward object-designation associations. However, this sense of indetermination does not necessarily prevent communication from taking place. We therefore argue that Rico Dalasam, by forging faltering ways with signs, orients to constant movement as a way of inhabiting the border and formulating alternative rules for re-existence. ———————————————————————————- TRANSISIOMATICIDADE E TRANSPERFORMANCES NO RAP QUEER BRASILEIRO: POR UMA ESTÉTICA ABJETA O rap queer tem tido grande repercussão no mundo homofóbico do hip-hop nos últimos tempos, especialmente no cenário contemporâneo musical de Nova York. Considerado por muitos como a nova sensação, os rappers queer têm desconstruído os modos considerados tradicionais de compor, falar e apresentar o rap ao fazerem uso mais abertamente de performances femininas, caracterizadas por ambivalência, hibridismo e resistência. Neste artigo, focalizamos como Rico Dalasam, um performer brasileiro contemporâneo, radicaliza esse tipo de ruptura, ao se engajar no que chamamos de “estética abjeta” Ela compõe uma paisagem semiótica espetacular, na qual sexualidades, gêneros, raças, etnias, estilos de roupa, cortes de cabelos, ritmos, línguas e registros se entrecruzam. Na verdade, transperformances e transidiomaticidade dominam seu trabalho, o qual abordamos por meio das noções de escala (CARR; LEMPERT, 2016) e indexicalidade metapragmática (SILVERSTEIN,1993) ao analisarmos as letras do rap, suas performances e sua recepção por audiências diferentes. O movimento analítico gera visibilidade para o atravessamento de recursos semióticos que subvertem a circulação de artefatos linguísticos e nãolinguísticos pelas fronteiras. Em particular, discutimos como o desempenho multissemiótico-desterritorializador de Dalasam confronta regimes epistemológicos e linguísticos modernistas, subvertendo o logocentrismo. O foco do estudo está no trânsito entre os chamados centro e periferia e nos significados enigmáticos gerados pela mistura de línguas e performances. Em sua totalidade, esses aspectos deixam os interactantes em um estado de incerteza, uma vez que os recursos reunidos não são diretamente inteligíveis em um sentido convencional, já que, muito frequentemente, evitam associações referenciais diretas a objetos. Contudo, esse sentido de indeterminação não necessariamente prejudica a comunicação. Argumentamos que Rico Dalasam, ao forjar modos vacilantes de usar signos, se coloca em movimentação constante como um modo de habitar a fronteira e de formular regras alternativas de reexistência. — Original em inglês.